The Impact of Corporate Layoff Announcements on Shareholder Wealth – Finnish Evidence from Years 2005-2008 - Tornikoski, Mikko (My University, 2011)
The purpose of this paper is to investigate the impact of corporate layoff announcements on stock returns in the Finnish stock market. In case of demand shifts, changes in a firm’s competitive intra-industry position or financial distress, layoffs may be an optimal way to adjust. Therefore, it is intriguing to investigate the impact of corporate layoff announcements on shareholders’ wealth. In this paper, two hypotheses are tested. The first one posits that stock returns are abnormally negative for those firms that state declining demand (DD) to be the reason behind layoffs and abnormally positive for the companies that conduct such an action to enhance efficiency (EE). The second hypothesis in turn states that the magnitude of the layoffs has an impact on the announcing firms’ stock returns. The event study methodology is being applied in order to empirically measure the impact of corporate layoff announcements on stock prices. Also the bootstrapping methodology is being used aside the conventional t-test to provide more trustworthy results. The study utilizes information on layoffs to classify announcements based on the cited reason for such decision from 2005 to 2008. The final sample contains 104 layoff announcements, out of which 47 observations are in the declining-demand subsample and 57 observations in the efficiency-enhancing subsample. The findings indicate that the stock prices react negatively on the announcement day when firms cite adverse markets conditions. Surprisingly, the results derived from the efficiency-enhancing subsample lead to similar conclusions. However, they show less negative reactions. Moreover, CAAR after 10 days is more negative for EE than for DD. As a result, the H1 hypothesis is only partially approved. In addition, the results do not show any statistical significance to support that the magnitude of the announcement would have an impact on stock returns. Thus, the H2 hypothesis is rejected.
Keywords: work force; layoff; abnormal returns; event study; bootstrapping; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|